Calcium hydroxide and niobium pentoxide treatment effects before MTA placement. (1st March 2022) - Sankeerthana, Kolli; Karthikeyan, Kittappa; Mahalaxmi, Sekar
Abstract: The aim of this study was to evaluate the effect of calcium hydroxide (CH) and niobium pentoxide (NP) pretreatment on pH, dentin microhardness and sealing of Mineral Trioxide Aggregate (MTA; Angelus). The pH of CH, NP and CH–NP (3:1) was evaluated in neutral and acidic simulated tissue fluid over 28 days. The Vickers microhardness was measured in forty 4 mm coronal root slices filled with pretreatment materials stored in medium for 1, 7, 28 days. Forty 10 mm roots were packed with pretreatment materials, irrigated after 24 h, then a 3 mm MTA plug was placed. Sealing ability was evaluated after 7 days using fluid filtration method. Statistics was performed using ANOVA and post hoc Tukey HSD tests. Addition of NP to CH maintained the alkalinity of CH, increased the microhardness of root dentin and reduced the microleakage. CH–NP can be effectively used as a pretreatment medicament in root canals requiring placement of MTA under acidic conditions.